POLA HIDUP PASIEN DIABETES MELLITUS TIPE II DI RS PKU MUHAMMADIYAH GOMBONG - Puspita Sari, Desi; -, Saryono; Sumarsih, Tri (LPPM STIKES MUHAMMADIYAH GOMBONG, 2014)
One disease that is closely associated with unhealthy lifestyle is diabetes mellitus. Healthy lifestyle is consuming a balanced nutritious diet with regular exercise. Diabetes mellitus is a degenerative disease marked by a rise in blood sugar levels (hyperglycemia) and high levels of sugar in the urine (glycosuria). The less attention to the poor lifestyle, the more people will be affected by DM. Based on medical record data in 2011-2012, patients with DM had increased to 200 patients in Inayah and Ward Barokah PKU Muhammadiyah Gombong Hospital. This aim of this research is Â to determine the lifestyle of patients with diabetes mellitus in PKU Muhamadiyah Gombong Hospital. This is a qualitative research using the phenomenological approach. The sampling method is purposive sampling method. The interview was done to 5 participants based on the inclusion and exclusion criteria. The patients who underwent treatment at PKU Muhammadiyah Gombong Hospital had a bad healthy lifestyle before illness. They consumed sweet food and drinks, but it was not balanced with doing exercises and activity patterns. Keywords: Lifestyle, Diabetes Mellitus